Closing the (nuclear) envelope on the genome: How nuclear lamins interact with promoters and modulate gene expression. (24th November 2013) - Collas, Philippe; Lund, Eivind G.; Oldenburg, Anja R.
<x xml:space="preserve">Abstract</x> The nuclear envelope shapes the functional organization of the nucleus. Increasing evidence indicates that one of its main components, the nuclear lamina, dynamically interacts with the genome, including the promoter region of specific genes. This seems to occur in a manner that accords developmental significance to these interactions. This essay addresses key issues raised by recent data on the association of nuclear lamins with the genome. We discuss how lamins interact with large chromatin domains and with spatially restricted regions on gene promoters. We address the relationship between these interactions, chromatin modifications and gene expression outcomes. Lamin‐genome contacts are redistributed after cell division and during stem cell differentiation, with evidence of lineage specificity. Thus, we also speculate on a developmental role of lamin interactions with specific genes. Finally, we highlight how concepts arising from this recent work lay the foundations of future challenges and investigations.